If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-4 + r) = -112 (-4 * 8 + r * 8) = -112 (-32 + 8r) = -112 Solving -32 + 8r = -112 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 8r = -112 + 32 Combine like terms: -32 + 32 = 0 0 + 8r = -112 + 32 8r = -112 + 32 Combine like terms: -112 + 32 = -80 8r = -80 Divide each side by '8'. r = -10 Simplifying r = -10
| 0.34*-70.6= | | 0=-16t^2+40t+12 | | 8x+2=3*x | | 1+6-(5+1)= | | a(4+3)= | | 7x-10=40x+1 | | 6x^4+5x^2-4=0 | | 7x-10=40x+q | | (a+12)(a^2-7a+7)= | | (N+3)(n+6)=0 | | ax-bx=12 | | cx+3h=58 | | 0=16-4x^2 | | b+4=12 | | 2m^2=-8-8m | | 6y^2-13y+6=0 | | .75x+3=9 | | -12(x-4)=-3(6x+2) | | -x-3=-4x-14 | | 0.65x+.05(8-x)=.10(-8) | | 3lx-5l-2x=10 | | x-1(3x-9)=-5 | | 4y=9x+4f | | a-5=2a | | x-1(3x-9)=5x | | 4x^2-32x=-60 | | a+1-5*6=b+56 | | -3(x-1)=2(1-2x) | | -8(1+5r)=11(-4r-3)-11 | | 5x+2y+(3x-y)+(2x-y)= | | abcdefg-hijklmn=42 | | y=p^2-2p+2 |